Penerapan Teknologi Sederhana Untuk Meningkatkan Produktivitas UMKM Kreatif Di Ungaran - Adhi Susano; Meida Rachmawati (Khidmah Nusantara, 2026)
Creative Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy but still face obstacles in adopting practical technologies that enhance productivity. This study aims to analyze the implementation of applied simple technologies limited to business management and digital marketing tools in creative MSMEs in Ungaran and to measure their impact on productivity improvement. The term simple technology in this study refers to smartphone-based point-of-sale (POS) systems, inventory management applications, basic accounting software, customer relationship management features, and digital marketing tools such as social media business features and marketplace integration, excluding production machinery or manufacturing automation. The research employs a qualitative case study approach supported by quantitative productivity indicators, involving 25 creative MSMEs from handicraft, culinary, and fashion sectors. Productivity improvement of 35.7% was derived from comparative analysis of revenue per employee, sales volume per month, and cost-efficiency ratio before and after technology adoption within a 3-month observation period. Data were validated through documentation review and triangulation of financial and operational records. The findings indicate that structured technology training and mentoring significantly accelerate adoption, achieving an 80% successful implementation rate. The study concludes that context-appropriate application of simple technologies constitutes a scalable and sustainable strategy to enhance the competitiveness of creative MSMEs in semi-urban regions.